2022
DOI: 10.29312/remexca.v13i28.3272
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la nanobiofortificación con hierro en el rendimiento y compuestos bioactivos en pepino

Abstract: El hierro (Fe) es un micronutriente indispensable para los seres vivos. No obstante, y a pesar de que es uno de los metales más abundantes en la corteza terrestres, existe baja disponibilidad para los cultivos, provocando un déficit en la alimentación de alrededor de dos millones de personas en el mundo. La nanobiofortificación puede mitigar esta deficiencia ya que su aplicación en los cultivos mejora la biosíntesis de compuestos bioactivos y propicia su bioacumulación. El objetivo de esta investigación fue ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The results in Table (6) showed that the cultivars showed significant differences in the fresh weight of vegetative growth, the Burren cultivar was significantly excelled on the rest of the cultivars and gave the highest average of the fresh weight of vegetative growth amounted to 312.67 g, while the cultivar Sifra gave an average of the fresh weight of vegetative growth amounted to 301.91 g, while it was in the Royal cultivar, which was 282.69 g. The results also showed that the water stress had a significant effect on the fresh weight of vegetative growth, where the treatment without stress recorded the highest rate of the fresh weight of vegetative growth and gave 335.92 g, followed by the treatment of stress during the germination stage and recorded the dry weight of vegetative growth amounted to 318.09 g, while the treatment of stress during the stage of vegetative growth recorded the lowest rate The fresh weight of vegetative growth was 248.09 g. The results also showed that the nano-fertilizer had a significant effect on the average fresh weight of vegetative growth, where the spraying with a concentration of 2g.L -1 excelled and gave the highest mean for the fresh weight of vegetative growth amounted to 310.09g, followed by the spraying treatment with a concentration of 1g.L -1 and gave an average of the fresh weight of vegetative growth amounted to 297.31g. While the treatment without spraying recorded the lowest average fresh weight of vegetative growth was 286.36 g. The interaction between the Burren cultivar and without stress also excelled and gave the highest rate of fresh weight of vegetative growth compared to other interaction treatments and recorded 350.31 g, while the fresh weight of vegetative growth decreased when the bi-interaction treatment consisting of (Royal cultivar and stress during the tuber formation stage) recorded dry weight of vegetative growth It was 221.33 g The results also showed the excelled of the bi-interaction treatment consisting of (Burren cultivar and spraying at a concentration of 2 g.L -1 ) and gave the highest mean of fresh weight of vegetative growth amounting to 323.90 gm, while the treatment (Royal cultivar without spraying) recorded the lowest mean of fresh weight of vegetative growth amounting to 264.44 gm Also, the bi-interaction treatment consisting of (treatment without stress and spraying at a concentration of 2g.l -1 ) was recorded and gave the highest rate of fresh weight of vegetative growth amounted to 353.09 g, while the treatment (stress during the tuber formation stage and without spraying) was recorded and gave the lowest rate of fresh weight of vegetative growth.…”
Section: Fresh Weight Of Vegetative Growth (G)mentioning
confidence: 99%
“…The results in Table (6) showed that the cultivars showed significant differences in the fresh weight of vegetative growth, the Burren cultivar was significantly excelled on the rest of the cultivars and gave the highest average of the fresh weight of vegetative growth amounted to 312.67 g, while the cultivar Sifra gave an average of the fresh weight of vegetative growth amounted to 301.91 g, while it was in the Royal cultivar, which was 282.69 g. The results also showed that the water stress had a significant effect on the fresh weight of vegetative growth, where the treatment without stress recorded the highest rate of the fresh weight of vegetative growth and gave 335.92 g, followed by the treatment of stress during the germination stage and recorded the dry weight of vegetative growth amounted to 318.09 g, while the treatment of stress during the stage of vegetative growth recorded the lowest rate The fresh weight of vegetative growth was 248.09 g. The results also showed that the nano-fertilizer had a significant effect on the average fresh weight of vegetative growth, where the spraying with a concentration of 2g.L -1 excelled and gave the highest mean for the fresh weight of vegetative growth amounted to 310.09g, followed by the spraying treatment with a concentration of 1g.L -1 and gave an average of the fresh weight of vegetative growth amounted to 297.31g. While the treatment without spraying recorded the lowest average fresh weight of vegetative growth was 286.36 g. The interaction between the Burren cultivar and without stress also excelled and gave the highest rate of fresh weight of vegetative growth compared to other interaction treatments and recorded 350.31 g, while the fresh weight of vegetative growth decreased when the bi-interaction treatment consisting of (Royal cultivar and stress during the tuber formation stage) recorded dry weight of vegetative growth It was 221.33 g The results also showed the excelled of the bi-interaction treatment consisting of (Burren cultivar and spraying at a concentration of 2 g.L -1 ) and gave the highest mean of fresh weight of vegetative growth amounting to 323.90 gm, while the treatment (Royal cultivar without spraying) recorded the lowest mean of fresh weight of vegetative growth amounting to 264.44 gm Also, the bi-interaction treatment consisting of (treatment without stress and spraying at a concentration of 2g.l -1 ) was recorded and gave the highest rate of fresh weight of vegetative growth amounted to 353.09 g, while the treatment (stress during the tuber formation stage and without spraying) was recorded and gave the lowest rate of fresh weight of vegetative growth.…”
Section: Fresh Weight Of Vegetative Growth (G)mentioning
confidence: 99%
“…The Zn content was determined by triacid digestion (Guillén-Enríquez et al, 2022). One gram of each sample was weighed on an analytical balance (HR-120), with an accuracy of 0.0001 g. The sample was then placed in a 250 mL beaker with boiling beads, and 25 mL of triazide mixture (1 L of HNO3, 100 mL of HCl, 25 mL of H2SO4) was added.…”
Section: Zinc Content Analysismentioning
confidence: 99%